Nursing competence in the Primary Care: a focus on the humanization of the work process - Lislaine Aparecida Fracolli; Danielle Freitas Alvim de Castro (O Mundo da Saúde)
The possibility of establishing skills to nursing practice in primary care is an important resource to support the formation of professionals. The National Policy of Humanization reaffirms the need to ensure comprehensive care to the population and enhance the health condition as a right of citizenship ascribed to people. The aim of this paper is to discuss the skills that are being taught in an undergraduate nursing course, pointing to those that support the practice of humanized health care. This is a qualitative research, whose methodological option was to use the Delphi Technique, with faculty and students at the School of Nursing of University of São Paulo for consideration of the list of skills built by Witt. The results showed that there is a consensus on the fact that the powers relating to the provision of assistance based on ethics, commitment and accountability to the citizens’ health and the services and expertise aimed at identifying problems and health needs are the most developed in this undergraduate Nursing course. We conclude that there is the purpose of making nursing training to look for strengthening of Primary Care and humanization of care.